2020
DOI: 10.2174/1567205017666201109095657
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid and Blood CX3CL1 as a Potential Biomarker in Early Diagnosis and Prognosis of Dementia

Abstract: Background: A growing body of evidence highlights the crucial role of neuroinflammation and chemokine involvement in cognitive impairment pathophysiology. Fractalkine (CX3CL1) appears to be a relevant causative factor in the development of dementia, particularly at the early stages of the disease. However, limited data are available on the levels of CX3CL1 in the cerebrospinal fluid (CSF) and blood. Additionally, to date, its utility as a biomarker for MCI or AD has not been studied. Objective: The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…1 Mean normalised protein expression values for the chemokines in controls and each of PPA groups in CSF. Significant differences with p values are shown on the graphs CCL3, and CX3CL1 in this group parallel previous studies in those with a typical AD clinical presentation [13][14][15][16][17][18]. CCL2 (MCP-1) is expressed by neurons, astrocytes, and microglia and has previously been shown to be raised in the CSF of people with typical AD including those with mild cognitive impairment (MCI) [13,14,19].…”
Section: Discussionsupporting
confidence: 85%
“…1 Mean normalised protein expression values for the chemokines in controls and each of PPA groups in CSF. Significant differences with p values are shown on the graphs CCL3, and CX3CL1 in this group parallel previous studies in those with a typical AD clinical presentation [13][14][15][16][17][18]. CCL2 (MCP-1) is expressed by neurons, astrocytes, and microglia and has previously been shown to be raised in the CSF of people with typical AD including those with mild cognitive impairment (MCI) [13,14,19].…”
Section: Discussionsupporting
confidence: 85%
“…In keeping with lvPPA being associated with underlying AD pathology, the ndings of increased CCL2, CCL3 and CX3CL1 in this group parallel previous studies in those with a typical AD clinical presentation (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). CCL2 (MCP-1) is expressed by neurons, astrocytes and microglia, and has previously been shown to be raised in the CSF of people with typical AD including those with mild cognitive impairment (MCI) (14)(15)(16).…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, from an AD perspective, CX3CL1 has also been shown to be upregulated in the hippocampus during memory-associated synaptic plasticity (23). Several studies have demonstrated signi cantly higher CSF concentrations of CX3CL1 in people with MCI and AD (20), with concentration being shown to differentiate MCI from controls with high sensitivity and speci city (24). Our study also showed a strong correlation with t-tau in lvPPA as well as in the controls and other groups, suggesting an association with increased neuronal damage particularly in the AD brain.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, due to the regulatory function in inflammation, this biomarker is a promising therapeutic target. A recent Polish study reported on the predictive ability of CX3CL1 as a biomarker in the early development of mild cognitive impairment (MCI) and AD 9 . In this study, significantly higher CSF and blood levels of CX3CL1 were found in MCI and AD patients compared to cognitively healthy controls.…”
Section: Supplemental Materialsmentioning
confidence: 99%